From Screens to Streams: Empowering 21st Century Entrepreneurs Through AI-Driven Business Models - Sixbert Sangwa; Paul Ruhamya; Dennis Ngobi; Placide Mutabazi (Science and Education, 2025)
This study examines how AI-driven business models can catalyze economic empowerment among African youth entrepreneurs, focusing on Rwanda as a case study. We investigate digital economy trends, theoretical perspectives, and empirical evidence to understand how AI adoption and digital engagement translate into income and opportunity for young people. We employ a mixed-methods convergent design, combining systematic literature review and international data analysis with youth-focused case studies in Rwanda. Advanced analytics (e.g. NLP of qualitative data, machine learning-based trend analysis) are used to identify success factors and barriers. Major findings show that when digital capital (skills, access) and supportive innovation ecosystems align (Echoing Rogers’s Diffusion of Innovations, Sarasvathy’s Effectuation, and Ragnedda’s Digital Capital theory), AI tools (e.g. fintech, EdTech, AgriTech) significantly boost entrepreneurial outcomes (Mashavira, 2024; Ferster, 2021, University of Copenhagen. (n.d.)). For example, digital platforms like Uganda’s AI-powered road-safety device or Senegal’s ADIA business-planning tool illustrate practical AI applications in local enterprises (International Trade Center, 2024; Gatera, 2025). We find that Rwanda’s proactive policies (e.g. National AI Policy, AI scaling hub) and growing ICT infrastructure have created a fertile ground for youth-led startups, although challenges remain in skills gaps and access (ICTWorks, 2023; Gatera, 2025). Implications span development economics, education, and technology policy: targeted AI training and entrepreneurship education can drive inclusive growth, but require cross-sector coordination. We conclude with strategic recommendations (for academia, NGOs, educators, government, youth enterprises) and propose a cross-sector implementation matrix to guide action. Future research directions look 10-15 years ahead at trends in AI innovation, evolving education models, and sustainable job creation in Africa’s digital economy.